The suitability of film for modelling the pragmatics of interaction: Exploring authenticity. (April 2020) - Ryan, Jonathon; Granville, Scott
Abstract: Previous studies have highlighted the potential of film to promote the development of L2 pragmatics by presenting to learners the types of authentic, contextually-appropriate language use routinely absent from textbooks. However, the issue of authenticity is multifaceted and there has been little if any exploration of authenticity in terms of larger sequences within scripted texts. Sequence authenticity is particularly relevant to learners, as it demonstrates how actions are achieved over multiple turns, and how utterances are designed to 'fit' with previous turns and how they shape the next turn; difficulties in this domain can prove highly problematic. To explore the pedagogical potential of general-release films, the present study analysed dialogue from 20 popular English-language movies, and reports findings relating to invitation sequences and the overall structuring practices found in phone call openings and closings. The findings reveal systematic and highly recurrent ways in which film dialogues tend to deviate from ordinary speech. These findings are discussed in terms of the conventions of narrative film and key principles of drama.